Proposiciones diferenciales sobre la existencia de conflictos entre potencias mundiales - Olmedo González, Hernán (El Colegio de México A.C., 2025)
The purpose of this article is to identify the bilateral international factors that significantly influence the existence of militarized conflicts between world powers. Taking all the inter-annual bilateral relations between world powers from 1816 to 2015 as units of analysis, this study applies logistic and linear regression statistical techniques to analyze the association between a series of potentially influential factors and the existence of different modalities of militarized conflicts between world powers. As a result, the study shows, on the one hand, that the various types of conflicts have different combinations of influencing factors and, on the other, that the combination of high levels of rivalry, military spending and low levels of commercial interdependence are factors that significantly affect the existence of a large part of the militarized conflicts between world powers.